ACCOUNTING INFORMATION SYSTEM (AIS) - Aura Safitri; Yusri Hazmi, Nurhayati, Zahra Firdausa Hasra (Adisam Publisher, 2024)
In the era of digitalization, entities are developing technologies that can be used in various fields. This technological advancement greatly affects efficiency and productivity, especially in the business sector. Business operations are influenced by the development of new products, diverse marketing processes, and advanced production processes aided by technology. In order to facilitate financial reporting, companies must also be agile in selecting financial reporting software. The use of Accounting Information Systems (AIS) can have positive impacts on a company, such as accuracy and speed in financial reporting, enabling investors to make informed investment decisions. AIS is a system used by management to manage a company. This study aims to provide a deeper understanding of the implementation of AIS for effective management. The research methodology employed is a literature review, utilizing various literature sources such as books, journals, articles, and other research materials. The study discusses the definition and role of AIS in company management, as well as its implementation in optimizing company performance. The findings highlight the importance of AIS in providing accurate and timely financial information, aiding decision-making processes and facilitating company transactions. Therefore, implementing AIS is crucial for companies to compete effectively in the business world.